DNA-stimulated ATPase activity on the lon (CapR) protein. - Charette, M F (1984)
The gene product of the pleiotropic lon (also called capR) locus in Escherichia coli, the CapR protein, is an ATP hydrolysis-dependent protease and a nonspecific nucleic acid-binding protein. We demonstrated that it is also a DNA-stimulated adenosine triphosphatase (ATPase). This new activity is distinct from the protease-associated ATPase activity and occurs in the absence of proteolytic substrate. The reaction requires the presence of a divalent cation and has a pH optimum of 8.0. The products of the reaction are ADP and inorganic phosphate. No adenylation or phosphorylation of the DNA or proteins was detected. The maximum rate of ATP hydrolysis occurs in the presence of supercoiled (form I) DNA. Relaxed circles (form II), double-stranded DNA, and single-stranded DNA are less effective in promoting ATPase activity, whereas RNA is inactive. The DNA-stimulated ATPase activity is inhibited by a mutationally altered form of the CapR protein called the CapR9 protein. The interaction of the CapR and CapR9 subunits suggests that this enzymatic activity of the CapR protein is oligomeric in the presence of DNA. Our in vitro experiments indicate a possible role for nucleic acids in the regulation of all lon (capR) activity.